Pinus sylvestris L. and other conifers as natural sources of ascorbic acid - Ain Raal; Katrin Nisuma; Andres Meos (GarVal Editorial Ltda., 2018)
Context: There is a widespread opinion that needles of conifers are a good source of ascorbic acid and may help to cure and prevent scurvy. Aims: To determine the content of ascorbic acid in needles and shoots of Pinus sylvestris, Picea abies, Juniperus communis and several other conifers. Methods: Ascorbic acid content was analyzed by HPLC: aminocolumn 250 mm x 4.6 mm, 5 µm; mobile phase acetonitrile and 0.05 M KH2PO4 (75:25), flow rate 1.0 mL/min, detection at 266 nm. Results: The fresh needles contained more (10.8 x 10-3%) of ascorbic acid than the fresh shoots (5.4 x 10-3%) of the same P. sylvestris tree. In needles collected during one year with monthly intervals from the same pine tree the content of vitamin C varied from 0.5 x 10-3% to 15.7 x 10-3%. The needles gathered in winter from November to March contained much more of ascorbic acid (5.2-15.7 x 10-3%) than needles collected during warmer season (0.5-2.8 x 10-3%). The fresh needles of compared conifers (n=11) contained ascorbic acid from 0% (Tuja occidentalis) to 15.0 x 10-3% (Tsuga canadensis), needles of J. communis contained ascorbic acid a little more (13.3 x 10-3%) than needles of P. sylvestris, P. abies and Microbiota decussata (9.0-10.8 x 10-3%). Conclusions: The concentration of ascorbic acid in needles and shoots of studied conifers is rather low if compared to other natural sources of vitamin C. Fresh plant material of P. sylvestris, P. abies and J. communis contained more ascorbic acid than frozen material. The concentration of ascorbic acid in needles of these three trees was higher than in shoots.